2000
DOI: 10.1021/ar960061v
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Catalysis of Epoxide Ring-Opening Reactions

Abstract: The discovery of the metal salen-catalyzed asymmetric ring-opening (ARO) of epoxides is chronicled. A screening approach was adopted for the identification of catalysts for the addition of TMSN(3) to meso-epoxides, and the chiral (salen)CrN(3) complex was identified as optimal. Kinetic and structural studies served to elucidate the mechanism of catalysis, which involves cooperative activation of both epoxide and azide by two different metal centers. Covalently linked bimetallic complexes were constructed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
665
0
22

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,185 publications
(702 citation statements)
references
References 28 publications
15
665
0
22
Order By: Relevance
“…32 In addition to diamide ligands, we also explored the use of ferrocene-derived Schiff base metal complexes for the ring-opening polymerization of cyclic esters. 17,[33][34][35][36] Schiff base metal complexes have found numerous uses in coordination chemistry and catalysis, [37][38][39][40][41][42] alkoxide yttrium complexes supported by such ligands being intensely researched as initiators for the ring-opening polymerization of cyclic esters. 17,[35][36][43][44][45][46][47][48][49][50] On the other hand, reports of structurally characterized alkyl or aryl rare earth complexes bearing an imine functionality in the backbone are rare, [51][52] the majority being represented by phosphinimine ligands.…”
Section: Introductionmentioning
confidence: 99%
“…32 In addition to diamide ligands, we also explored the use of ferrocene-derived Schiff base metal complexes for the ring-opening polymerization of cyclic esters. 17,[33][34][35][36] Schiff base metal complexes have found numerous uses in coordination chemistry and catalysis, [37][38][39][40][41][42] alkoxide yttrium complexes supported by such ligands being intensely researched as initiators for the ring-opening polymerization of cyclic esters. 17,[35][36][43][44][45][46][47][48][49][50] On the other hand, reports of structurally characterized alkyl or aryl rare earth complexes bearing an imine functionality in the backbone are rare, [51][52] the majority being represented by phosphinimine ligands.…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest in this context that binuclear analogues of many catalysts that rely on bimetallic interactions show enhanced activity when compared to monomeric species, examples include certain Ru and Os diporphyrin H 2 evolving catalysts with cofacial orientation (24,25). In one noteworthy case, Jones and coworkers (26,27) showed that a "bisalen" analogue of Jacobsen's Co-(salen) catalyst for hydrolytic kinetic resolution of racemic epoxides (a reaction that also shows a second-order dependence on catalyst concentration) maintained activity when linked to a solid support, whereas the immobilized monomer was essentially inactive (26)(27)(28). Because one of our goals is construction of a catalytic cobaloxime-modified electrode for water reduction, we have investigated the reactivity of a covalently-linked dicobalt complex.…”
mentioning
confidence: 99%
“…It has already been demonstrated that the oligo(salamo) helical complexes show unique physical properties and reactivities [98][99][100][101], and the dynamic helicity control would be useful for switching of the chiroptical properties of the helical structures. The catalytic reactivity of the chiral metallosalen scaffold [84][85][86][87] could also be incorporated into the oligo(salamo) helical structures, which could dynamically switch the enantioselectivity of the catalytic reactions. In this sense, the oligo(salen)-type helical structures are promising to provide an excellent platform that can drive the dynamic switching of various kinds of chiral functions.…”
Section: Discussionmentioning
confidence: 99%
“…In order to control the helicity in a more rational and predictable fashion, we focused on chiral salen derivatives, which have two chiral carbon centers at the ethylene bridge of the salen ligands. It is well known that some chiral salen complexes act as excellent enantioselective catalysts (up to 99% ee) [84][85][86][87] and this indicates that the chiral twist is perfectly controlled in these systems. The chiral twist can be discussed in terms of the N-C-C-N dihedral angles (+60 deg or −60 deg) of the ethylene bridge in the salen ligands.…”
Section: Strategymentioning
confidence: 94%